Complications of microwave ablation in patients with persistent/recurrent hyperparathyroidism after surgical or ablative treatment - Ying Wei; Zhen-long Zhao; Jie Wu; Shi-liang Cao; Li-li Peng; Yan Li; Ming-an Yu (International Journal of Hyperthermia)
Objective To evaluate the complications associated with microwave ablation (MWA) in treating persistent/recurrent hyperparathyroidism (HPT) post-surgical or ablative treatments.Materials and methods From January 2015 to December 2022, 87 persistent/recurrent HPT patients (primary HPT [PHPT]: secondary HPT [SHPT] = 13:74) who underwent MWA after surgical or ablative treatment were studied. Grouping was based on ablation order (initial vs. re-MWA), prior treatment (parathyroidectomy [PTX] vs. MWA), and etiology (PHPT vs. SHPT). The study focused on documenting and comparing treatment complications and analyzing major complication risk factors.Result Among the 87 patients, the overall complication rate was 17.6% (15/87), with major complications at 13.8% (12/87) and minor complications at 3.4% (3/87). Major complications included recurrent laryngeal nerve (RLN) palsy (12.6%) and Horner syndrome (1.1%), while minor complications were limited to hematoma (3.4%). Severe hypocalcemia noted in 21.6% of SHPT patients. No significant differences in major complication rates were observed between initial and re-MWA groups (10.7% vs. 13.8%, p = 0.455), PTX and MWA groups (12.5% vs. 15.4%, p = 0.770), or PHPT and SHPT groups (15.4% vs. 13.5%, p > 0.999). Risk factors for RLN palsy included ablation of superior and large parathyroid glands (>1.7 cm). All patients recovered spontaneously except for one with permanent RLN palsy in the PTX group (2.1%).Conclusion Complication rates for MWA post-surgical or ablative treatments were comparable to initial MWA rates. Most complications were transient, indicating MWA as a viable and safe treatment option for persistent/recurrent HPT patients.